An adaptive multi-spline refinement algorithm in simulation based sailboat trajectory optimization using onboard multi-core computer systems - Dębski, Roman (Zielona Góra: Uniwersytet Zielonogórski)
A new dynamic programming based parallel algorithm adapted to on-board heterogeneous computers for simulation based trajectory optimization is studied in the context of "high-performance sailing". The algorithm uses a new discrete space of continuously differentiable functions called the "multi-splines" as its search space representation.
Keywords: dynamic programming; black-box optimization; heterogeneous computing; micro HPC platform; cubic Hermite splines